Boundary Control Behaviors of Multiple Low-Cost AUVs Using Acoustic Communication - Mohammed Tarnini; Saverio Iacoponi; Andrea Infanti; Cesare Stefanini; Giulia de Masi; Federico Renda (IEEE Access)
This study presents acoustic-based methods for the formation control of multiple autonomous underwater vehicles (AUVs). This study proposes two different models for implementing boundary and path control on low-cost AUVs using acoustic communication and a single central acoustic beacon. Both models are based on the history of relative range and do not rely on the full knowledge of the AUVs states based on a centralized beacon system. Two methods are presented: the Range Variation-Based (RVB) model completely relies on range data obtained by acoustic modems, whereas the Heading Estimation-Based (HEB) model uses ranges and range rates to estimate the position of the central boundary beacon and perform assigned behaviors. The models are tested on two formation control behaviors: Fencing and Milling. Fencing behavior ensures AUVs return within predefined boundaries, while Milling enables the AUVs to move cyclically on a predefined path around the beacon. Models are validated by successfully performing the boundary control behaviors in simulations, pool tests, including artificial underwater currents, and field tests conducted in the ocean. All tests were performed with fully autonomous platforms, and no external input or sensor was provided to the AUVs during validation. Quantitative and qualitative analyses are presented in the study, focusing on the effect and application of a multi-robot system.